2022
DOI: 10.1371/journal.pgph.0000466
|View full text |Cite
|
Sign up to set email alerts
|

Performance of HIV rapid testing algorithm in Nigeria: Findings from a household-based Nigeria HIV/AIDS Indicator and Impact Survey (NAIIS)

Abstract: Background The Nigeria AIDS Indicator and Impact Survey (NAIIS), a cross-sectional household survey, was conducted in 2018 with primary objectives to estimate HIV prevalence, HIV-1 incidence, and status of UNAIDS 90-90-90 cascade. We conducted retrospective analysis of the performance of HIV rapid tests and the national HIV testing algorithm used in Nigeria. Methods The national algorithm included Determine HIV-1/2 as test 1 (T1), Unigold HIV-1/2 as test 2 (T2), and StatPak HIV-1/2 as the tie-breaker test (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…[19][20][21] A retrospective study in Nigeria using household survey data found that the performance of the two-test strategy in a low prevalence setting of about 1.4% was poor with a PPV of 94% and a false-positive rate of 5.5%. 22 This positive predictive value is similar to a modelling study assessing the accuracy of the 2015 and 2019 WHO HIV testing algorithms, which was 95.4% using a two-assay testing strategy. 19 Considering that the recommendation to use dual HIV/syphilis RDTs in ANC was released only in 2019, 6 23 its adoption by 21 countries has been encouraging.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[19][20][21] A retrospective study in Nigeria using household survey data found that the performance of the two-test strategy in a low prevalence setting of about 1.4% was poor with a PPV of 94% and a false-positive rate of 5.5%. 22 This positive predictive value is similar to a modelling study assessing the accuracy of the 2015 and 2019 WHO HIV testing algorithms, which was 95.4% using a two-assay testing strategy. 19 Considering that the recommendation to use dual HIV/syphilis RDTs in ANC was released only in 2019, 6 23 its adoption by 21 countries has been encouraging.…”
Section: Discussionsupporting
confidence: 73%
“…We found that among low-prevalence countries (n=34), a significant proportion (41%) still use a suboptimal testing strategy with two assays to make an HIV-positive diagnosis, which will increase the likelihood of false-positive diagnosis 19–21. A retrospective study in Nigeria using household survey data found that the performance of the two-test strategy in a low prevalence setting of about 1.4% was poor with a PPV of 94% and a false-positive rate of 5.5% 22. This positive predictive value is similar to a modelling study assessing the accuracy of the 2015 and 2019 WHO HIV testing algorithms, which was 95.4% using a two-assay testing strategy 19…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of this study also showed a low discordant rate of 1.1% between Tests 1 and 2, from the retrospective study that included testing data from 492,880 individual HTS clients in the field. In comparison, the prospective study showed discordant rates ranging from 0.4% to 2.8% in the field and laboratory, all of which were significantly lower than the discordant rate PLOS GLOBAL PUBLIC HEALTH of 43.4% observed in the NAIIS [8], as well as below the allowable discordance threshold of less than 5% recommended by WHO [2]. Thus suggesting that the observations from the NAIIS were specific to the survey and not representative of the field performance of the algorithm.…”
Section: Discussionmentioning
confidence: 60%
“…The survey showed a much lower national HIV prevalence status of 1.4% in Nigeria compared to the 4.1% from previous surveys [6,7]. However, analysis of the NAIIS data indicated that the concordance rate between Test 1 and Test 2 was low (56.5%), and the positive predictive value (PPV) of HIV-positive diagnosis was 94.5% when confirmed with Geenius supplementary assay [8]. The World Health Organization (WHO), using mathematical modeling, recommends three consecutive test algorithm requiring all three reactive tests if the national HIV prevalence is <5% due to anticipated low PPV [2].…”
Section: Introductionmentioning
confidence: 71%
“…Globally, HIV diagnosis is frequently performed using algorithms based on HIV rapid tests (RTs). In general, RTs have emerged as the preferred method for HIV diagnosis in low-and-middleincome-countries (LMICS) due to the performance characteristics of HIV RT and the added operational benefits, such as ease of use and interpretation, storage at ambient temperature, and no special laboratory equipment requirements (18).…”
Section: Introductionmentioning
confidence: 99%